Factors Influencing Adherence to Disease Modifying Antirheumatic Drugs and Its Effects on Disease Activity in Rheumatoid Arthritis Patient (Journal of Chittagong Medical College Teachers' Association, 2020)
Background: Non-adherence in patients with Rheumatoid Arthritis (RA) using Disease Modifying Antirheumatic Drugs (DMARDs) will not only affect the patient’s disease activity, but also the rheuma-tologist’s treatment decisions, and lead to higher health care costs. Poor adherence has been shown to be linked to different factors in different studies. There is paucity of study among the RA patients of Bangladesh in this issue. This study was conducted to evaluate the factors influencing adherence to DMARDs and its effects on disease activity in RA patient.Materials and methods: It was a hospital based cross-sectional study. Total 107 diagnosed cases of RA, on DMRDs at least for 3 months were included from Rheumatology Clinics of Medicine and Physical Medicine Department of Chittagong Medical College Hospital (CMCH) from January 2018 to December 2018. Severity of RA was assessed by Disease Activity Score (DAS-28) while drug adherence was measured by Morisky Medication Adherence Scale-8 (MMAS-8) questionnaire. The Beliefs about Medicines Questionnaire (BMQ) was used to assess beliefs about the necessity of medication and concerns about it.Results: Out of the 107 RA patients there was female predominance with a male to female ratio of 1:2.15 and mean age was 45.53±12.13 years with a range of 18-69 years. Non-adherence with DMARDs was found among 80.4% of cases. Non adherent patients had significantly higher disease activity as measured by DAS-28. Except belief about medication no other socio-demographic and disease related factors were associated with adherence level. Higher adherence was associated with stronger perceptions of necessity of treatment and less concerns about treatment.Conclusion: Frequency of low adherence among RA patients was high and patients with lower medication adherence tended to have higher disease activity. The strongest relation with adherence was found to be beliefs about the necessity of the medication and it is modifiable. This provides hope to improve adherence.JCMCTA 2019 ; 30 (2) : 62-69